2013
DOI: 10.1007/s11745-013-3854-7
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Training Increases Leptin Expression in the Retroperitoneal Adipose Tissue of Rats Fed with a High‐Sugar Diet

Abstract: The presence of leptin receptors in white adipose tissue (WAT) suggests a type of peripheral control during the development of obesity and other metabolic disorders. Both diet composition and exercise influence serum leptin; however, the effect of their combination on long-term WAT leptin metabolism is unknown. In this study, rats fed with standard or high-sugar diets (HSD) were simultaneously subjected to running training for 4- and 8-week periods, and the retroperitoneal WAT (rWAT) was evaluated for adipocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
5
21
0
1
Order By: Relevance
“…In addition, the overconsumption of high‐carbohydrate diets modulates cellular pathways controlling de novo lipogenesis, leading to greater adiposity . Although their final body weights were identical, we demonstrated that the corporal composition was different in rats fed a HSD, with increasing fat mass according to previous results from our group . In a study conducted by de Lima et al.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the overconsumption of high‐carbohydrate diets modulates cellular pathways controlling de novo lipogenesis, leading to greater adiposity . Although their final body weights were identical, we demonstrated that the corporal composition was different in rats fed a HSD, with increasing fat mass according to previous results from our group . In a study conducted by de Lima et al.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the overconsumption of high-carbohydrate diets modulates cellular pathways controlling de novo lipogenesis, leading to greater adiposity [13]. Although their final body weights were identical, we demonstrated that the corporal composition was different in rats fed a HSD, with increasing fat mass according to previous results from our group [26,29]. In a study conducted by de Lima et al [7], an increase in the Lee index was observed after a 19-week HSD feeding period in the same experimental model; however, the time point that these alterations began remained unclear.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The excessive development of visceral white adipose tissue (AT) is an important determinant of metabolic syndrome, a complication that frequently occurs in obese subjects [6]. Among the intra-abdominal depots, epididymal (EPI) and retroperitoneal (RET) AT are considered as visceral depots and have been largely used for metabolic regulation studies [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of exercise training towards reducing circulating adipocytokine levels may be important to other tissue responses, but the effects of ObR on vascular tissue in exercised animals are unknown since most studies examined the effect of exercise training on leptin and its receptors in adipose tissue and skeletal muscle [79,80]. In addition, a reduction in AdipoR1 has been reported in skeletal muscle and adipose tissue in experimental models of obesity, and exercise training was effective to prevent this alteration [81,82].…”
Section: Discussionmentioning
confidence: 99%